Do general principles govern all science? - Rolston, Holmes, 1932-2025, interviewee; Kuhn, Robert Lawrence, interviewer; The Kuhn Foundation; Getzels Gordon Productions, producer (Colorado State University. Libraries, 2012)
Robert Lawrence Kuhn interviews: Geoffrey West, physicist, Santa Fe Institute, on complex adaptive systems. Martin Rees, astrophysics, Cambridge University, on complex systems resulting from simple laws. Stuart Kauffman, theoretical biologist, Santa Fe Institute and University of Calgary, on super-critical complex systems, molecular and economic. Holmes Rolston, III, philosopher, Colorado State University, on three Big Bangs: matter-energy, life, human mind, genesis of cognitive complexity, revealing a Logos in creation. (Rolston interview starts at 15 minutes, 20 seconds.) David Deutsch, physicist, Oxford University, on good explanations in general systems theory. Among the conclusions: As we get closer to truth, everything seems more interconnected. God is consistent with these general principles, but not required for them.
Closer to truth: do general principles govern all science?
Robert Lawrence Kuhn interviews: Geoffrey West, physicist, Santa Fe Institute, on complex adaptive systems. Martin Rees, astrophysics, Cambridge University, on complex systems resulting from simple laws. Stuart Kauffman, theoretical biologist, Santa Fe Institute and University of Calgary, on super-critical complex systems, molecular and economic. Holmes Rolston, III, philosopher, Colorado State University, on three Big Bangs: matter-energy, life, human mind, genesis of cognitive complexity, revealing a Logos in creation. (Rolston interview starts at 15 minutes, 20 seconds.). David Deutsch, physicist, Oxford University, on good explanations in general systems theory.
Among the conclusions: As we get closer to truth, everything seems more interconnected. God is consistent with these general principles, but not required for them.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Rolston, Holmes, 1932-2025